Changing language teaching through language testing : - Cheng, Liying (Cambridge University Press, 2005)
There has been growing interest in recent years in the influence of tests on teaching and learning - a phenomenon commonly referred to as 'washback'. Despite persistent assertions about its nature and scope, empirical studies investigating test washback are still limited in number, and few of these make use of both qualitative and quantitative methods in washback research.